Between hearths and volcanic ash: The SU 13 palimpsest of the Oscurusciuto rock shelter (Ginosa – Southern Italy): Analytical and interpretative questions. (28th September 2016) - Spagnolo, Vincenzo; Marciani, Giulia; Aureli, Daniele; Berna, Francesco; Boscato, Paolo; Ranaldo, Filomena; Ronchitelli, Annamaria
Abstract: The Oscurusciuto rock shelter, located in the ravine of Ginosa (Taranto), is one of the key sites for the study of Neanderthal groups in Southern Italy. The rich stratigraphic sequence of the site, which is ascribable entirely to the Middle Palaeolithic, is rich in anthropic remains and combustion structures, attesting occupation by Neanderthals during MIS 3. This paper is focused on the study of Stratigraphic Unit (SU) 13, made up of a compact sandy sediment mixed with pyroclastic sediment derived from the underlying tephra level (SU 14). The latter has been identified as Monte Epomeo green tuff (dated Ar/Ar 55 ± 2 ka). The first stable human occupation of the shelter after tephra deposition is represented by unit 13. Our aim here is that of separating the Stratigraphic Unit into its main components so as to obtain a high temporal resolution on the activities which took place in this SU, and to reconstruct the individual events which formed the palimpsest. In order to fulfil these objectives, a multidisciplinary approach was needed through which data could be integrated from the microstratigraphy of the hearths; from the technological study of the lithic industries; from the individuation of the Raw Material Units (RMUs); from refitting and co-joining and from spatial analysis (GIS science/tool). The integration of these analytical methods reveals that SU 13 of the Oscurusciuto rock shelter was the product of a series of events ascribable to a short time span. This layer was formed by sediment aggradation and cementation (e.g., brecciation) processes. Human activities contributed to the sediment build up with the introduction of wood ash, lithic raw materials and bones. The results show the importance of using integrated research methods in order to identify short anthropic events within a palimpsest.